Development of a simplified version of the smoking rationalization belief scale for Chinese male smokers - Zhang, Lingyun; Chen, Hao; Mao, Yimeng; Zheng, Shichen; Zheng, Pinpin (Frontiers in Psychiatry, 2023)
Objective The goal of this study was to simplify the smoking rationalization belief (SRB) scale among Chinese male smokers and provide a convenient measuring tool with good reliability and validity to promote the assessment and further intervention of SRB among smokers. Methods Through purposive sampling, a questionnaire survey was conducted among adult male smokers in three districts in Shanghai, and 1,307 valid questionnaires were collected. Exploratory factor analysis was used to analyze the simplified scale, and Pearson correlation analysis, multiple linear regression, and Cronbach’s α were used to test the reliability and validity of the simplified scale. Results The SRB scale was simplified from 26 items to 8 items and had good overall reliability (Cronbach’s α = 0.757). There was a strong correlation between the simplified scale and the original scale (P < 0.001, r = 0.911), and the scores of SRB measured by the two scales were both negatively associated with a willingness to quit smoking (P < 0.001), which reflected the practical effectiveness of the simplified version. Conclusion The simplified version of the SRB scale showed good reliability and validity among Chinese smokers, which facilitates smoking cessation-related research and practice.